Minerais Pesados dos Depósitos Aluviais do Rio Paraná e sua Implicação Paleohidrológica - SANTOS, MANOEL LUIZ DOS; GASPARETTO, NELSON VICENTE LOVATTO (Pesquisas em Geociências, 2008)
Heavy-mineral analyses have been widely used in order to study the origin of sediments. Although it is not often used in stratigraphic studies, heavy minerals may be very important to correlate events, and facies associations in sedimentary basins. In this study, the rate-of-occurrence analysis of these accessory minerals and their texture intends to correlate the related fluvial deposits with both the present and the past channel of the Paraná River, and those deposits occurring in its hydrografic basin. Thirty samples were collected from the Paraná River deposits and its slopes, from Paranaíba (MS) to Porto Rico (PR) areas. The assembly of transparent heavy minerals is formed by zircon, tourmaline, staurolite, kyanite, epidote, rutile, sillimanite, andalusite, garnet, pyroxene, and amphibole. The analysis of the mineralogical and textural maturity of this assembly have shown a significant differentiation between the deposits of the Paraná river alluvial system and, it proved to be a useful tool for paleohydrological studies.